Effect of L-arginine, dimercaptosuccinic acid (DMSA) and the association of L-arginine and DMSA on tissue lead mobilization and blood pressure level in plumbism - Malvezzi, C.K. [UNESP]; Moreira, E.G. [UNESP]; Vassilieff, I. [UNESP]; Vassilieff, V.S. [UNESP]; Cordellini, S. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2001)
Lead (Pb)-induced hypertension is characterized by an increase in reactive oxygen species (ROS) and a decrease in nitric oxide (NO). In the present study we evaluated the effect of L-arginine (NO precursor), dimercaptosuccinic acid (DMSA, a chelating agent and ROS scavenger), and the association of L-arginine/DMSA on tissue Pb mobilization and blood pressure levels in plumbism. Tissue Pb levels and blood pressure evolution were evaluated in rats exposed to: 1) Pb (750 ppm, in drinking water, for 70 days), 2) Pb plus water for 30 more days, 3) Pb plus DMSA (50 mg kg-1 day-1, po), L-arginine (0.6%, in drinking water), and the combination of L-arginine/DMSA for 30 more days, and 4) their respective matching controls. Pb exposure increased Pb levels in the blood, liver, femur, kidney and aorta. Pb levels in tissues decreased after cessation of Pb administration, except in the aorta. These levels did not reach those observed in nonintoxicated rats. All treatments mobilized Pb from the kidney, femur and liver. Pb mobilization from the aorta was only effective with the L-arginine/DMSA treatment. Blood Pb concentrations in Pb-treated groups were not different from those of the Pb/water group. Pb increased blood pressure starting from the 5th week. L-arginine and DMSA treatments (4th week) and the combination of L-arginine/DMSA (3rd and 4th weeks) decreased blood pressure levels of intoxicated rats. These levels did not reach those of nonintoxicated rats. Treatment with L-arginine/DMSA was more effective than the isolated treatments in mobilizing Pb from tissues and in reducing the blood pressure of intoxicated rats.
Keywords: L-arginine; DMSA; tissue lead mobilization; plumbism; blood pressure; rat